1994
DOI: 10.1182/blood.v83.7.1980.bloodjournal8371980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of T-cell depletion as graft-versus-host disease prophylaxis on engraftment, relapse, and disease-free survival in unrelated marrow transplantation for chronic myelogenous leukemia

Abstract: Between January 1988 and March 1993, 48 patients received T-cell- depleted marrow grafts from unrelated donors as treatment for chronic myelogenous leukemia (CML). The median age of the population was 31.7 years (range 5.4 to 53) with 17 of 48 patients greater than 40 years of age. Twenty-seven patients were transplanted in chronic phase, 17 in accelerated phase, and 4 in blast crisis. All patients received a standardized preparative regimen of cyclophosphamide, high-dose cytosine arabinoside, methylprednisolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…We suspect that apart from the conditioning, residual TCRgd cells and other immune cells contribute to robust engraftment and a very low rate of graft failure. It has been shown that infusion of activated gd T cells can promote engraftment 35,36 without causing GvHD, even in the MHC-mismatched situation. 37 Patients going into transplantation with active viral infections had the worst outcomes in our cohort, as shown previously in patients with SCID undergoing HSCT in which infants (>3.5 months of age) with infection had a poor survival in comparison with those with resolved infections or those without prior infection (50% vs 82% vs 90%).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that apart from the conditioning, residual TCRgd cells and other immune cells contribute to robust engraftment and a very low rate of graft failure. It has been shown that infusion of activated gd T cells can promote engraftment 35,36 without causing GvHD, even in the MHC-mismatched situation. 37 Patients going into transplantation with active viral infections had the worst outcomes in our cohort, as shown previously in patients with SCID undergoing HSCT in which infants (>3.5 months of age) with infection had a poor survival in comparison with those with resolved infections or those without prior infection (50% vs 82% vs 90%).…”
Section: Discussionmentioning
confidence: 99%
“…However, graft-versus-host disease (GVHD) and the toxicity of ablative conditioning have limited the widespread clinical application of this approach (3,4). T cell depletion (TCD) of BM prevents GVHD, but is associated with significantly impaired engraftment (5)(6)(7). We were the first to identify a CD8 ϩ /TCR Ϫ BM population that facilitates hematopoietic stem cell (HSC) engraftment across MHC barriers without causing GVHD (8)(9)(10).…”
mentioning
confidence: 99%
“…However, the role of MUD transplants for CML is still limited by the fact that the incidence of acute and chronic graft‐versus‐host disease (GVHD) is greater than after an HLA‐identical sibling transplant (Enright et al , 1996; Hansen et al , 1998). Depletion of T cells from the donor marrow can reduce the incidence of acute and chronic GVHD (Mackinnon et al , 1990; Drobyski et al , 1994; Spencer et al , 1995a), but is associated with delayed immune reconstitution and an increased risk of relapse and graft failure (Goldman et al , 1988; Martin et al , 1988; Marks et al , 1993; Ochs et al , 1995). Consequently, it has been unclear what role, if any, T‐cell depletion (TCD) strategies should play in the prevention of GVHD after MUD transplantation.…”
mentioning
confidence: 99%